Re-envisioning the Church through the "Eyes" of the Woman Clothed with the Sun and the Bride in John’s Apocalypse - Saulina, Chakrita M. (Veritas : Jurnal Teologi dan Pelayanan, 2023)
The book of Revelation is dominated by many enigmatic images and symbols that spark a variety of interpretations and speculations. Among these puzzling images, the feminine symbols in the second half of the book are worth noting: the woman clothed with the sun in Revelation 12, the whore in Revelation 17, and the bride in Revelation 21. Their meanings are often debated. Some feminist scholars argue that these images evoke violence towards women and are full of androcentric language. Others, however, by underlining the metaphoric nature of these female symbols, refute this claim. This study aims to provide a fresh interpretation of this debate by looking more closely at the web of John’s metaphors and narrative system and utilizing both historical-critical and narrative approaches. This work argues that these female figures convey positive images of women and inclusivity in the Lamb’s Church. Moreover, the woman clothed with the sun and the bride have a vital role in John’s apocalypse. The link between these two metaphors—the transformation of the woman and becoming the bride—offers an important message to contemporary churches, including churches in Indonesia, in navigating the world and overcoming crises.